Characteristics of the Optimal Cognitive Behavioral Analysis System of Psychotherapy (CBASP) Therapist Role - McCullough, James P. (Frontiers in Psychiatry, 2021)
The characteristics of the optimal CBASP therapist role for the treatment of the Persistent Depressive Disorder patient (chronic depression) is delineated in this paper. This paper contains the opinions and experiences of the creator of CBASP who has developed and revised the model over more than 4 decades. The paper is not a rigorous study nor a review of rigorous studies. The difficulties of the patient are briefly discussed and then the characteristics of the optimal clinical role are presented The clinical role of CBASP, the only model to have been developed specifically to treat the chronically depressive patient, is unique in the field of psychotherapy. Four role categories describing the behavior of the best therapists are presented and discussed: (1) the therapist is able to enact a Disciplined Personal Involvement clinical role with the patient; (2) the therapist is able to implement an acquisition-learning approach to therapeutic administration; (3) The practitioner is able to adhere to the standards of CBASP technique administration; and finally, (4) the clinician is able to implement several facilitative interpersonal skills.